SCIENTIFIC COMMUNICATIONS IN SPORTS INFORMATICS - Tursunov , Muhriddin Muhammad ugli (Educational Research in Universal Sciences, 2023)
The article examines the history of the formation of communities and the development of scientific communications in the field of application of mathematical methods, computer science and digital technologies in sports in Russia and in the world.